Energy Saving Through Design Optimization Of Induction Motors - Rini Nur Hasanah (Fakultas Teknik, Universitas Brawijaya, 2009)
In this article, basic concepts and general procedures in induction motor design and optimization are described. Beginning with the definition of design problem, some design objectives are distinguished based on the type of power supplies as well as motor applications. Some basic equations relating output characteristics to motor physical dimensions are given and two different design approaches are highlighted. The design optimization is explained by giving the definition of design variables and parameters, objective functions, constraint functions and the general technique of optimization. As examples, two motor designs with special objectives, including loss-minimization as well as wide speed-range operation, are presented.Keywords: energy saving, design, optimization, induction motor